Exact and heuristic methods in combinatorial optimization: a study on the linear ordering and the maximum diversity problem - Martí, Rafael; Reinelt, Gerhard (Applied mathematical sciences, 2022)
1 Introduction -- 2 Heuristic Methods -- 3 Meta-Heuristics -- 4 Branch-and-Bound -- 5 Branch-and-Cut -- 6 The Linear Ordering Polytope -- 7 Further Aspects -- References -- Index.